Penerapan Pembelajaran Eksperimen untuk Memahami Konsep Perubahan Wujud Benda pada Siswa Kelas V Sekolah Dasar - Fadilatul Firdausiah; Muhammad Suwignyo Prayogo; Silvia Santi Ekik Prayustin (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
This study aims to analyze the effectiveness of experiential learning in improving fifth-grade elementary school students' understanding of the concept of changes in the form of objects. The research methodology used is literature review, which involves the analysis and synthesis of various research findings, scientific articles, and related journals published in the coming years (2020–2025). In the context of science education in elementary schools, experiential learning is very important in helping students understand abstract concepts concretely through careful observation and analysis activities. Experimental methods such as melting ice, evaporating water, or forming dew are effective ways to connect theory with student experience. Based on the results of the study, experimental methods can improve students' conceptual understanding, science process skills, and knowledge, such as curiosity, thoroughness, and responsibility for learning activities. In addition, experiential learning can help students become more motivated to learn and actively participate in class throughout the learning process. However, a number of factors, such as teacher guidance, the availability of tools and equipment, and the ability of teachers to supervise students' experimental activities in class, affect the success of the program. Therefore, teachers must conduct experiments that are meaningful, relevant to everyday life, and appropriate to the characteristics of students in the school. Therefore, the use of experience-based learning can be an effective strategy to improve the quality of science teaching, especially material on physical objects, so that students can understand scientific concepts clearly and concisely.